2023
DOI: 10.1155/2023/7443226
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofol: A Novel Alternative to Propofol in Clinical Intravenous Anesthesia?

Abstract: Ciprofol is a novel compound that was independently developed in China. According to the Chinese product instructions approved by the China National Medical Products Administration and the information of official website, indications for ciprofol include sedation and anesthesia during the surgical/procedure of nontracheal intubation, induction and maintenance of general anesthesia, and sedation during intensive care. Ciprofol is a short-acting intravenous sedative based on the structural modification of propof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Ciprofol is a short-acting intravenous sedative based on the structural modi cation of propofol, whose main mechanism is to activate the postsynaptic GABA-A-Clchannel complex, which causes hyperpolarization of nerve cell membrane through chloride ion in ux, thus causing central nervous system inhibition [15][16][17]. The high selective binding ability of ciprofol to its receptor enables it to achieve the same sedative and anesthetic effects as propofol at a lower dose [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Ciprofol is a short-acting intravenous sedative based on the structural modi cation of propofol, whose main mechanism is to activate the postsynaptic GABA-A-Clchannel complex, which causes hyperpolarization of nerve cell membrane through chloride ion in ux, thus causing central nervous system inhibition [15][16][17]. The high selective binding ability of ciprofol to its receptor enables it to achieve the same sedative and anesthetic effects as propofol at a lower dose [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Ciprofol is a rapid‐onset anesthetic that takes effect in a dose‐dependent manner, and its efficacy is about four to five times that of propofol 12 . The anesthetic effect falls between that of ciprofol and that of propofol 7 . In the induction of general anesthesia for patients undergoing elective surgery, ciprofol has shown the advantages of rapid onset, minimal response to tracheal intubation, and stable vital signs 11,23 .…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Ciprofol is extensively metabolized after administration; this primarily occurs in the liver through phase I cytochrome P450 (CYP) 2B6 and phase II glucuronosyltransferase 1A9 (UGT1A9). 7,16 A mass balance and biotransformation study showed that the major metabolites in plasma were glucuronic acid-M4 (~79.3% of the total plasma radiation exposure) and that those in urine were M4 and M5-1 (accounting for 51.6% and 19.3% of the dose, respectively) after a single intravenous dose of 0.4 mg/0.8 μCi/kg [ 14 C] ciprofol. 17 By contrast, unchanged ciprofol accounted for only 3.97% of the total radiation exposure and was not detected in urine, which further demonstrated that the major metabolite was M4 and was mainly excreted via the kidneys (84.59%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ciprofol exhibits wide tissue distribution, and it has been reported that approximately 95% of the drug is bound to plasma proteins [7]. It is primarily metabolized in the liver by phase II glucuronosyltransferases (UGTs), with UGT1A9 being the main enzyme responsible for the conversion of ciprofol to its major metabolite, M4.…”
Section: Introductionmentioning
confidence: 99%